The impact of economic openness on the economic growth of Central and Eastern European countries after the systemic transformation - Jakub Garncarz (International Entrepreneurship Review)
Objective: The objective of the article is to examine the impact of foreign trade on economic growth in countries opening up their economies as a result of their separation from the blocs of socialist countries.